A review of hydro-hegemony and transboundary water governance. Issue 11 (13th October 2022) - Hayat, Shakeel; Gupta, Joyeeta; Vegelin, Courtney; Jamali, Hameed
Abstract: This review paper is an attempt to analyze the existing literature on hydro-hegemony (HH) theory, which has emerged to explain transboundary water interactions. The literature highlights that the conventional water interaction literature inadequately deals with three important factors: (i) asymmetric power relations, (ii) varying intensities of conflict, and (iii) the importance of the geographical location of riparian states. Since its emergence, it has evolved both in theory development and in application to transboundary basins. Although an attempt has been made earlier for reviewing, organizing and evaluating the overall literature on HH, the review itself is somehow silent on the hegemonic approaches to assess its contribution to the transboundary water governance literature and to identify the existing and future research gaps. This paper, however, not just addresses these omissions to (i) review the scholarly literature on HH; (ii) explore the challenges associated with power, cooperation, and conflict; and (iii) identify and explore potential trends in HH theory, but it also gives special attention to the hegemonic approaches within states' boundaries and the ingredients to enrich the theory and research agenda of HH. HIGHLIGHTS: The conventional water interaction literature inadequately deals with three important factors (asymmetric power relations, varying intensities of conflict, and the importance of the geographical location of riparian states). This paper addresses to review the scholarly literature on HH; explore the challenges associated with power, cooperation, and conflict; identify and explore potential trends in HH theory, and reviews the HH within states' boundaries.